2010
DOI: 10.1103/physreva.82.033201
|View full text |Cite
|
Sign up to set email alerts
|

Probing photoelectron multiple interferences via Fourier spectroscopy in energetic photoionization ofXe@C60

Abstract: Considering the photoionization of the Xe@C 60 endohedral compound, we study in detail the ionization cross sections of various levels of the system at energies higher than the plasmon resonance region. Five classes of single-electron levels are identified depending on their spectral character. Each class engenders distinct oscillations in the cross section, emerging from the interference between active ionization modes specific to that class. Analysis of the cross sections based on their Fourier transforms un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…To further enrich the interference, the part of the amplitude emanated from the Zn region will reflect from the hull edges as a consequence of the modified continuum of Zn due to the surrounding C 60 potential. The detailed expression of the general structure of this LDA matrix element has already been derived [27,28]. Following Ref.…”
Section: A the Lda Contextmentioning
confidence: 99%
“…To further enrich the interference, the part of the amplitude emanated from the Zn region will reflect from the hull edges as a consequence of the modified continuum of Zn due to the surrounding C 60 potential. The detailed expression of the general structure of this LDA matrix element has already been derived [27,28]. Following Ref.…”
Section: A the Lda Contextmentioning
confidence: 99%
“…Many aspects of atoms confined in fullerenes have been studied in the recent past [21][22][23][24][25][26][27]. The effect of fullerene confinement on the photoionization time delay was studied very recently; it was found that confinement-induced correlation influences the temporal evolution of the photoelectron from different hybridized states of Ar confined within C 60 , Ar@C 60 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Photoionization results emanated from this LDA method, and from its time dependent (TDLDA) version at appropriate energies where many-electron effects dominate, have agreed well with experiments both in low energy plasmonic [2,17] and high energy oscillatory [18] regions for free C 60 . Further, it has recently been shown that the oscillation signals in the Fourier reciprocal space of our single photoionization TDLDA results for Xe@C 60 [19] in the Xe 4d giant resonance range are qualitatively well reproduced [20] by the double photoionization measurements of Xe@C 60 + [4]. Particular other insights obtained from our TDLDA method include the prediction of (a) the oscillator strength transfer from the C 60 plasmon to enhance the ionization of the confined atom [21,22], (b) the existence of atom-fullerene hybrid levels of unusual spectral behavior [23], and (c) the significant reverse-modification of captor fullerene's own ionization signal by the encaged atom [24].…”
Section: Introductionmentioning
confidence: 59%